2013
DOI: 10.1021/ic4004033
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Electronic and Steric Tuning of the Ligand in the Spin State and Catalytic Oxidation Ability of the FeII(Pytacn) Family of Complexes

Abstract: A family of iron complexes with the general formula [Fe(II)((R,R)'Pytacn)(X)2](n+) is described, where (R,R)'Pytacn is the tetradentate ligand 1-[(4-R'-6-R-2-pyridyl)methyl]-4,7-dimethyl-1,4,7-triazacyclononane, R refers to the group at the α-position of the pyridine, R' corresponds to the group at the γ-position, and X denotes CH3CN or CF3SO3. Herein, we study the influence of the pyridine substituents R and R' on the electronic properties of the coordinated iron center by a combination of structural and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 106 publications
7
95
0
Order By: Relevance
“…That is, more electron-withdrawing pyridine substitutents raise T ½ and stabilize the low-spin states of the complexes. Similar results were obtained in solution for two series of complexes of polydentate ligands, [Fe(Py 4´R tacn)(NCMe) 2 ] 2+ [37,92] and [Fe(stybp R ) 2 ] 2+ [93] (Scheme 7). In both cases, electron-withdrawing substituents on the 4-pyridyl ligand donors were observed to lower the room temperature magnetic moment or to raise T ½ , both consistent with stabilization of the low-spin state.…”
Section: Electronic Influence Of Ligand Substituents On Metal Ion Spisupporting
confidence: 79%
See 2 more Smart Citations
“…That is, more electron-withdrawing pyridine substitutents raise T ½ and stabilize the low-spin states of the complexes. Similar results were obtained in solution for two series of complexes of polydentate ligands, [Fe(Py 4´R tacn)(NCMe) 2 ] 2+ [37,92] and [Fe(stybp R ) 2 ] 2+ [93] (Scheme 7). In both cases, electron-withdrawing substituents on the 4-pyridyl ligand donors were observed to lower the room temperature magnetic moment or to raise T ½ , both consistent with stabilization of the low-spin state.…”
Section: Electronic Influence Of Ligand Substituents On Metal Ion Spisupporting
confidence: 79%
“…The unsubstituted macrocyclic complex [Fe(Pytacn)(NCMe) 2 ] 2+ is predominantly low-spin at room temperature in CD 3 CN, but three analogues [Fe(Py 6´R tacn)(NCMe) 2 ] 2+ bearing substituents at the pyridyl C6 position are all high-spin under the same conditions [37]. Unsubstituted [Fe(1-bpp) 2 ] 2+ (Scheme 2) is SCO-active, with T ½ = 248 K in (CD 3 ) 2 CO [38], but [Fe(R 2 -1-bpp) 2 ] 2+ are fully high-spin in the same solvent when R = Ph or iPr [39].…”
Section: Steric Influence Of Ligand Substituents On Metal Ion Spin Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, the search for a "universal" functional, which reliably predicts absolute spin-state energies goes on. Meanwhile, the series of Pytacn systems reported by Prat [41] is an attractive test bed for exploring relative spin-state energetics.…”
Section: Resultsmentioning
confidence: 99%
“…This gives us some hope that a relatively simple DFT protocol may be able to reproduce quite subtle features. [40] A recent paper by Prat et al [41] provides such an exacting test. The Here, we report a DFT study on these systems to see whether we can correlate the observed trend in magnetic moment with easily-computed energy differences.…”
Section: Introductionmentioning
confidence: 99%